Microfinance client protection in Asia and the Pacific lessons from ADB-smart campaign training programs. - Shinozaki, Shigehiro (Metro Manila, Philippines Asian Development Bank, 2017)
Slower economic growth globally and regulatory tightening in finance has complicated access to finance for vulnerable groups, including low-income households and small businesses. Limited financial access for these groups requires diversified financing modalities accessible to them, addressing the balanced development of banking and nonbank finance industries.
Keywords: Economic development; Privatization -- Asia; Microfinance -- Asia; Electronic books